PENERAPAN METODE ROLE PLAY UNTUK MENGEMBANGKAN KEMAMPUAN BERBICARA BAHASA INGGRIS GURU SD IT ANNUUR GEMOLONG - Retno Tri Vulandari, Arumsari, Saly Kurnia Octaviani & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
The aim of this research is to improve speaking skill of elementary teacher by using Role Play. . Data of this research uses pre â test and post â test of 30 teachers in SD IT ANNUR Gemolong Sragen. Meanwhile, this research was conducted using proportional stratified random sampling for taking its data sample andindependent sample t-testfor analyzing its data. According to the research result, the average of pre-test in 4th grade, 5th grade and 6thgrade (before any treatment) is lower than the post test. The data analysis shows that the average of pre-test is 54 and post-test is 72 for the teachers of 4th grade, the pre-test is 51 and post-test is 73,5 for teachers of 5th grade, the pre-test is 49,5 and post-test is 82 for the teachers of 6th grade. Students had improvement in understanding the materials after Role Play Method was given. It means that Role Play Method can improve teachersâ English speaking skill.Keywords: Teaching, English Teaching Method, Teaching Speaking, Role Play Method